2008
DOI: 10.1055/s-2008-1074554
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate Pattern inIsatis tinctoriaandI. indigoticaSeeds

Abstract: The glucosinolate patterns in seeds of five ISATIS TINCTORIA and two ISATIS INDIGOTICA accessions were assessed with a recently developed and validated LC-MS assay for direct analysis of glucosinolates without prior desulfatation. Glucosinolate peaks were identified with in-source fragmentation and detection of the sulfate anion ( M/Z = 97), and by MS/MS experiments. The glucosinolate patterns of the seeds showed characteristic differences compared to leaves. Glucoisatisin and epiglucoisatisin were diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The glucosinolate pattern of the seeds extract showed differences when compared to the extract obtained from the rosette leaves. In fact, the extracts obtained from I. tinctoria frozen and liophylized rosette leaves, mainly contained indolic glucosinolates including glucobrassicin, neoglucobrassicin, sulfoglucobrassicin, and glucotropaeolin ( Figure 7) [49,50]. The analysis carried out by the same authors also showed that the glucosinolate content in the leaf samples was higher than that of the seed samples.…”
Section: Glucosinolatesmentioning
confidence: 91%
“…The glucosinolate pattern of the seeds extract showed differences when compared to the extract obtained from the rosette leaves. In fact, the extracts obtained from I. tinctoria frozen and liophylized rosette leaves, mainly contained indolic glucosinolates including glucobrassicin, neoglucobrassicin, sulfoglucobrassicin, and glucotropaeolin ( Figure 7) [49,50]. The analysis carried out by the same authors also showed that the glucosinolate content in the leaf samples was higher than that of the seed samples.…”
Section: Glucosinolatesmentioning
confidence: 91%
“…Given our ongoing studies on indigoferous Isatis species [7][8][9][10], the draft monograph, and in particular the HPLC assay, drew our attention because of the extremely poor solubility of indigo. Another point that needed some investigation was the fact that > 97% of this drug remained undefined.…”
Section: Fidmentioning
confidence: 99%
“…Over the last decades, more than 100 bioactive constituents have been identified in methanolic extracts of I. tinctoria leaves and roots, including numerous alkaloids, fatty acids, and carotenoids (Mohn et al, 2009), as well as phenylpropanoid derivatives, such as flavonoids, hydroxyl‐cinnamic and hydroxyl‐benzoic acid derivatives, or mono‐ and oligo‐lignols (Nguyen et al, 2017). Especially, the glucosinolates, indole‐derived compounds, have attracted interest for their prospective medical properties (Mohn and Hamburger, 2008; Nguyen et al, 2017). For instance, indirubin, a bis‐indole alkaloid, was reported to mitigate expression of the influenza infection marker RANTES (regulated on activation, normal T cell expressed and secreted) in a bronchitis cell model (Mak et al, 2004; Sethi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%